Exploring utilitarian and hedonic antecedents for adopting information from a recommendation agent and unplanned purchase behaviour. Issue 1 (2nd January 2016) - Huang, Li-Ting
Abstract : Research indicated that in order for properly utilizing recommendation agents (RAs), customers must rationally evaluate capability and suggestions of RAs during the interaction process. However, enjoying interactive processes and interface is also important. Methods for increasing user enjoyment of RAs are yet unknown. This study investigated the influences of utilitarian and hedonic factors on intention to adopt RAs suggestions and their antecedents. Involvement influences relative importance of utilitarian and hedonic factors. Contrary to common assumptions, customers may make unplanned purchases, rather than rational purchase. A field experiment with 2 × 2 × 2 factorial design reveals main findings. First, information diagnosticity and enjoyment enhance adoption intention simultaneously. Information diagnosticity is more important than enjoyment. Diagnosticity was determined by outcome similarity, and enjoyment was determined by both outcome similarity and atmospherics. The context of interacting with RAs is important. Outcome similarity even directly affects adoption intention. Second, highly involved users considered enjoyment and diagnosticity when forming adoption intentions, while users with low involvement only considered enjoyment. Third, information cascades altered the relationship between adoption intention and unplanned purchases. Most customers change selection after seeing ratings from other customers, even if they originally strongly want to adoption suggestion from RAs. Theoretical and managerial implications are proposed.